Offshore Wind Floating System Demonstrator - Request for Proposal - ETI (ETI, 2015)
This project draws upon earlier ETI studies.These showed that floating foundations could be very attractive, by allowing the UK to access higher wind sites that are reasonably close to shore. Our analysis suggests that floating offshore wind has the medium to long term potential to deliver attractive energy costs.The Glosten Associates, a US-based navel architecture and marine engineering firm have designed a tension leg platform (TLP) floating system demonstrator through a Front End Engineering Design (FEED) Study.
The aim of the Project is to accelerate the market introduction of floating foundations for offshore wind farms and break down the barriers to their deployment.The required outcome of the Project is the manufacture and testing of a floating foundation that is integrated with an existing state of the art wind turbine at full size, rather than demonstration solely of manufacturing technology or a floating concept at smaller scale.The ETI recognises that different Respondents will propose different technologies and different project approaches.
The outcomes for this floating system demonstrator Project are to:
Design, construct and install a floating system demonstrator by late 2015 / early 2016 (using an existing installation vessel at a near shore and high wind (up to around 10 m/s) site with water depth between 60-100m and a tidal range and wave profile typical of the UK West coast;
Operate the system for a period of at least two years (to the end of 2017) to:
Demonstrate that the system can operate with high yield and be maintained without the need for ETI to support the construction of a new installation vessel;
Verify the system technical and economic performance predicted by the system models developed at the design stage;
Pull forward commercialisation of the enabling technologies to deploy the abundant near shore, 60-100m water depth, and high wind speed resources in the UK by at least 3 years;
Operate the system for up to a further 8 years, to provide a platform for further developments and revenue from electricity generation
Keywords: Offshore Wind; RENEWABLE ENERGY SOURCES (Wind Energy)